The epigenetic landscape: An evolving concept - Henikoff, Steven (Frontiers in Epigenetics and Epigenomics, 2023)
The epigenetic landscape was a visual metaphor introduced in the mid-twentieth century to illustrate the genetic control of embryonic differentiation. Although the popular understanding of epigenetics has since expanded to include gene and chromosomal mechanisms in all contexts, the landscape metaphor provides a unifying concept centered around processes that establish and maintain cellular memory. However, over the decades the term epigenetics has been also used to describe some non-genetic processes that bear little or no resemblance to the traditional concept of an epigenetic landscape. By establishing Frontiers in Epigenetics and Epigenomics, we aim to provide authors and readers a forum and an outlet for research that is centered around the original concept of an epigenetic landscape. Thanks in large part to exciting advances in epigenomic technologies, we expect that a deeper understanding of cellular memory will translate into new strategies for medicine, agriculture, and environmental health.